ANALISIS NILAI TUKAR NELAYAN (NTN) PANCING ULUR DI NEGERI KAWA KABUPATEN SERAM BAGIAN BARAT MALUKU - Nanlohy, Hellen; Rindiani, Rindiani; Saiful, Saiful (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
The fishermen's exchange analysis is a process of evaluating and assessing the economic performance of fishermen, including income, costs, and profits. This analysis is useful for identifying sources of income so that improvements and expansions can be made and optimizing fishermen's costs, so that they can increase profits. This research aims to analyze the Fishermen's Exchange Rate (NTN) of longline fishermen and to analyze the Fishermen's Exchange Rate Index (INTN) of longline fishing in Kawa Village, West Seram Regency. Data analysis was conducted through qualitative descriptive methods. This data aims to understand the characteristics of the respondents, while quantitative descriptive data analysis is used to calculate the income from fisheries, non-fisheries, expenditures from fisheries and non-fisheries, and household consumption, as well as to analyze the Fishermen's Exchange Rate (NTN) and the Fishermen's Exchange Rate Index (INTN) of longline fishermen in Kawa. The results of the study show that the average fishery business income obtained by fishermen from March to May 2024 is Rp. 6,680,417. The average non-fishery business income is Rp. 9,104,443. The average expenditure for fisheries business from March to May was Rp. 4,293,841, the average non-fishery business expenditure was Rp. 8,136,109, and the average expenditure for household consumption was Rp. 1,191,126. Meanwhile, the average non-consumption expenditure is Rp. 678,952. This indicates that the NTN of longline fishermen in Kawa Village is >1, where fishing households have a sufficient level of welfare to meet their primary needs and can also fulfill their non-primary needs.